Custom-made ocular prosthesis for a pediatric patient with unilateral anopthalmia: A case report - Saurabh Shrivastava; Surendra Agarwal; Kirti Jajoo Shrivastava; Parimala tyagi (Wolters Kluwer Medknow Publications, 2013)
Congenitally missing eye, often called as anopthalmia, is a rare condition. This causes disfigurement of the face, which poses psychological effect on children, making them emotionally weak and conscious which, in turn, causes anxiety, stress, and depression at an early age in life. The custom-made ocular prostheses should thus be provided as soon as possible to help children improve their social acceptance. We present a case of 9-year-old boy who reported with congenital anopthalmia of right eye, which was then restored with custom-made ocular prosthesis.